Influence of feeding system, stage of lactation and genetic types on ?9-desaturase activity in caprine milk - Impemba G.; Cifuni G.F.; Di Trana A. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The objectives of the present study were to evaluate the influences of feeding system, stage of lactation and genetic types on the product/substrate ratio of fatty acids (C10:1/C10:0; C12:1/C12:0; C14:1/C14:0; C16:1/C16:0; C18:1/C18:0; CLA/C18:1t11) and on the Desaturation Index (DI) as indicators of ?9-desaturase activity in caprine milk fat. Experiment 1: Four groups of lactating goats were fed with the following diets: natural pasture (P), pasture plus maize and broad beans (PMB), pasture plus barley and chickpeas (PBC), and hay plus mixed grains (HG). The product/substrate ratios and DI were affected (P<0.01) by the nutritional treatments. In the PMB fed goats C10:1/C10:0 and C18:1/C18:0 ratios were higher than those observed in the other groups. The highest values for C14:1/C14:0; C16:1/C16:0; CLA /C18:1t11 ratios and DI were observed in P feeding system. Experiment 2: Milk samples from lactating goats were collected every fifteen days starting 85 DIM till 175 DIM. The stage of lactation significantly affects C10:1/C10:0, C14:1/C14:0, C16:1/C16:0 and C18:1/C18:0 ratios. No differences were found for CLA/C18:1t11 ratio and DI during lactation. Experiment 3: Milk samples were obtained from four different genetic types of goats (Maltese, Red Syrian, Girgentana and Cashmere) in mid lactation. Genetic type did not affect product/substrate ratios except for C10:1/C10:0; C12:1/C12:0 ratio. The Cashmere genetic type exhibited higher ?9-desaturase activity for C10:1/C10:0 and C12:1/C12:0 ratios than other breeds. In conclusion, product/substrate ratios and DI, parameters that indirectly measured ?9-desaturase activity, were affected by feeding system; only some ratios were influenced by stage of lactation; the genetic types affect only C10:1/C10:0; C12:1/C12:0 ratios. Keywords: ?9-desaturase, goat milk, feeding system, stage of lactation, genetic types.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)